(3GdeUHGM TQM GdeaJGMs - (3Ydj Hf eMeO Hf Ydj, GdeYQha HGdTQja GdLQLGfj,J (B816 (3g` s; (3GdScGcj , SQGL GdOjf CHh jYbhH jhSa Hf CHj HcQ Hf eMeO Hf Ydj GdScGcj GdNhGQRej GdMfaj, GdScGcj,J (B626 (3g` s ((3Ydi Hf efUhQ Hf YHO Gdedc s)
(3ChdgG (B:s
(3fMeOc Gddge Ydi eG gOjJfG Edjg hHYO , abO WGdeG LGd ai UOQi Cf CQJH ddbSe GdKGdK ef eaJGM GdYdhe TQMkG jPdd UYGHg s
(3BNQgG (B:s
(3hgPG BNQ eG jSQ Gddg JYGdi Hefg hdWag ef cTa ahGFO gPG GdYde fLR GdaQGZ ef JCdjag ChGSW ThGd ef TghQ SfI (B803 s
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdJGSYs
(3JHUQI GdYfhGf (B:s
(3TQMs
Keywords: (3GdHdGZIs